Vitamin C effect on mitoxantrone-induced cytotoxicity in human breast cancer cell lines. - Eliana Guerriero; Angela Sorice; Francesca Capone; Virginia Napolitano; Giovanni Colonna; Gabriella Storti; Giuseppe Castello; Susan Costantini (PLoS ONE)
In recent years the use of natural dietary antioxidants to minimize the cytotoxicity and the damage induced in normal tissues by antitumor agents is gaining consideration. In literature, it is reported that vitamin C exhibits some degree of antineoplastic activity whereas Mitoxantrone (MTZ) is a synthetic anti-cancer drug with significant clinical effectiveness in the treatment of human malignancies but with severe side effects. Therefore, we have investigated the effect of vitamin C alone or combined with MTZ on MDA-MB231 and MCF7 human breast cancer cell lines to analyze their dose-effect on the tumor cellular growth, cellular death, cell cycle and cell signaling. Our results have evidenced that there is a dose-dependence on the inhibition of the breast carcinoma cell lines, MCF7 and MDA-MB231, treated with vitamin C and MTZ. Moreover, their combination induces: i) a cytotoxic effect by apoptotic death, ii) a mild G2/M elongation and iii) H2AX and mild PI3K activation. Hence, the formulation of vitamin C with MTZ induces a higher cytotoxicity level on tumor cells compared to a disjointed treatment. We have also found that the vitamin C enhances the MTZ effect allowing the utilization of lower chemotherapic concentrations in comparison to the single treatments.